KONTEKS YANG MENDASARI PETUTUR DALAM MEMAHAMI TUTURAN BERIMPLIKASI PERINTAH PADA ANIME BOFURI: I DON’T WANT TO GET HURT. SO I’LL MAX OUT MY DEFENSE EPISODE 1-12 - Susanti Susanti; Arza Aibonotika; Adisthi Martha Yohani (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: This study describes the utterances that have command implications in anime. This study aims to explain what underlies that the speaker understands the speech that contains the implications of the command conveyed by the addressee by understanding a context. The data in this study is the anime Bofuri: I Don't Want To Get Hurt. So I'll Max Out My Defense Episode 1-12. This study used descriptive qualitative method. The data analysis technique used in this study is to identify utterances that contain command implications, group them into sentences and describe what underlies that the speaker understands the meaning that the utterances have command implications. The results of this study found three contexts that underlie that the speaker understands an utterance. Where for the most part there is a shared knowledge context.Key Words: Command Implication, Context, Anime